Design and Development of CYO with Adjustable Smoke Volume. Issue 4 (May 2019) - Zhan, Jianbo; Wang, Hao; Zheng, Han; Yu, Tingting; Xie, Jiao; Li, Geng; Yu, Zhenhua; Zhang, Ying; Wang, Tao; Yue, Baoshan; Wang, Xu; Yu, Jiang; et al.
Abstract: In order to realize the adjustable and controllable smoke volume in the process of cigarettes' combustion and satisfy the different tar taste needs of consumers, a connector which can adjust the smoke volume was designed in this paper. By adjusting the angle of two rotatable sector surfaces, the tar can be controlled by adjusting the size of the air passage inside the intake passage. The physical parameters of the connector are calculated by ANSYS software, and the connecting effect is simulated. CYO cigarettes connected by the very connector are verified. The results show that the connector achieves the sticky effect and the tightness similar to the conventional cigarettes. Internal control sector can be easily rotated, and there is no obvious gap at the splice. There is no obvious leakage at the splice and connecting point during the smoking process. There is no significant difference between smoking evaluation and smoke detection with conventional cigarettes, and the ideal design effect is achieved.